Phylogenetic placement of Carrhotus Thorell, 1891 with three new species from Sri Lanka (Araneae: Salticidae) - Satkunanathan, Abira; Benjamin, Suresh P. (European Journal of Taxonomy, 2022)
The Sri Lankan species of the genus Carrhotus Thorell,1891 have remained taxonomically unrevised. The present study reviews all species of the genus in the island. Here we describe and diagnose three new species: Carrhotus albosetosus sp. nov. (♀), C. atratus sp. nov. (♂♀) and C. lobatus sp. nov. (♂). Further, C. silanthi Caleb, 2020 is reported in Sri Lanka for the first time. Carrhotus taprobanicus Simon, 1902 and C. viduus (C.L. Koch, 1846) are redescribed based on material from Sri Lanka. A key to the Carrhotus species in Sri Lanka is given.